Utilization and Processing of Starfruit into Various Food Products in Watesari Village, Balongbendo District, Sidoarjo Regency - Yani Ambari; Cindy Nadia; Dyah Mega Purwanti; Karina Putri; Nivia Fajar; Rita Amalia; Shintia Ifadah; Sholihul Anami; Sukarno Tejo; Wahyu Agtian (LPPM Universitas Ma Chung, 2022)
Starfruit is a fruit plant in the form of a tree originating from Malaysia, then spread widely to various other tropical countries including Indonesia. Sweet starfruit has various benefits for the health of the body. The content in star fruit can also be used for the prevention of diseases including getting rid of sore throat, cough, and fever, suppressing diabetic symptoms, also reducing high cholesterol. The processing of star fruit into various food products namely jam, ice cream, jelly candy, and pudding is carried out by the community service team of the Bachelor of Pharmacy Study Program, at Anwar Medika University. This utilization and processing are two of the tangible forms of improving the Watesari Village’s economy. The activities include counselling, processing, and distribution of various food products from star fruit. The activities that were carried out received a positive response from the Village Headman and Watesari Village residents. The Watesari Village community was very enthusiastic when distributing various food products made from star fruit.